2006
DOI: 10.1007/bf02931579
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa inducing rice resistance againstRhizoctonia solani: Production of salicylic acid and peroxidases

Abstract: Three isolates of Pseudomonas aeruginosa were used for seed treatment of rice; all showed plant growth promoting activity and induced systemic resistance in rice against Rhizoctonia solani G5 and increased seed yield. Production of salicylic acid (Sal) by P. aeruginosa both in vitro and in vivo was quantified with high performance liquid chromatography. All three isolates produced more Sal in King's B broth than in induced roots. Using a split root system, more Sal accumulated in root tissues of bacterized sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 31 publications
1
22
0
4
Order By: Relevance
“…P. aeruginosa UPMP3 has been reported to trigger induced systemic resistance (ISR) and upregulation of defence-related genes in relation to Ganoderma infection in oil palm seedlings (Sapak 2006;Sathyapriya et al 2011). Studies using Pseudomonas aeruginosa have described similar effects on other crops such as rice and tobacco (Geert et al 1999;Saikia et al 2006). Pseudomonas strains have also been reported to produce antibiotic compounds and the well-known antifungal compound 2,4-diacetylphloroglucinol (DAPG), but they were reported to not affect AMF performance in combination Hameeda et al 2007;Siasou et al 2009).…”
Section: Discussionmentioning
confidence: 89%
“…P. aeruginosa UPMP3 has been reported to trigger induced systemic resistance (ISR) and upregulation of defence-related genes in relation to Ganoderma infection in oil palm seedlings (Sapak 2006;Sathyapriya et al 2011). Studies using Pseudomonas aeruginosa have described similar effects on other crops such as rice and tobacco (Geert et al 1999;Saikia et al 2006). Pseudomonas strains have also been reported to produce antibiotic compounds and the well-known antifungal compound 2,4-diacetylphloroglucinol (DAPG), but they were reported to not affect AMF performance in combination Hameeda et al 2007;Siasou et al 2009).…”
Section: Discussionmentioning
confidence: 89%
“…Among these enzymes can be highlighted chitinases, lipoxygenases, peroxidases, and glucanases. Plants express the activity of peroxidase during pathogen-host interaction (Saikia et al 2006), where this enzyme has been implicated in the oxidation of phenols (Schmid and Feucht 1980), lignification (Saparrat and Guillen 2005), plant protection (Hammerschmidt et al 1982), and elongation of plant cells (Goldberg et al 1986). Increased activity of peroxidase has been correlated with resistance in many plant species, including rice and wheat (Young et al 1995).…”
Section: Induced Systemic Resistance As a Mechanism Of Disease Supprementioning
confidence: 99%
“…In several studies, the quantification of activity of enzymes involved in the induction of resistance has been used as a parameter to assess the induction mechanism (biotic or abiotic) involved (Knorzera et al 1999;Campos et al 2004;Nakkeeran et al 2006;Silva et al 2004;Halfeld-Vieira et al 2006;Saikia et al 2006). The increase in activity and accumulation of these enzymes depend mainly on the inducing agent but also the genotype of the plant, physiological conditions, and the pathogen (Tuzun 2001).…”
Section: Induced Systemic Resistance As a Mechanism Of Disease Supprementioning
confidence: 99%
“…In other host plants, Saikia et al (2006) reported that rice seed treatment with three different isolates of P. aeruginosa promoted plant growth and induced resistance against Rhizoctonia solani, whereas Bae et al (2009) reported that T. hamatum isolateDIS219bwas endophytic on cacao and led to plant growth promotion. These results demonstrate how diverse the responses to biological control are, depending on the strains of the pathogen and biocontrol agents, as well as the host plants.…”
Section: Effect Of Chili Seed Treatment On Relative Plant Heightmentioning
confidence: 97%